Clinical and Molecular Epidemiology of Invasive Group B Streptococcus Disease among Infants, China - Wenjing Ji; Haiying Liu; Shabir A. Madhi; Marianne Cunnington; Zilu Zhang; Ziyaad Dangor; Haijian Zhou; Xiaoping Mu; Zhengjiang Jin; Aimin Wang; Xiaosong Qin; Chunyan Gao; et al. (Emerging Infectious Diseases, 2019)
Invasive group B Streptococcus (GBS) remains a leading cause of illness and death among infants globally. We conducted prospective and retrospective laboratory-based surveillance of GBS-positive cultures from infants <3 months of age in 18 hospitals across China during January 1, 2015–December 31, 2017. The overall incidence of GBS was 0.31 (95% CI 0.27–0.36) cases/1,000 live births; incidence was 0–0.76 cases/1,000 live births across participating hospitals. The case-fatality rate was 2.3%. We estimated 13,604 cases of GBS and 1,142 GBS–associated deaths in infants <90 days of age annually in China. GBS isolates were most commonly serotype III (61.5%) and clonal complex 17 (40.6%). Enhanced active surveillance and implementation of preventive strategies, such as maternal GBS vaccination, warrants further investigation in China to help prevent these infections.